Multi-layer coordinated optimization of integrated energy system with electric vehicles based on feedback correction - Jia, Shiduo; Kang, Xiaoning; Cui, Jinxu; Tian, Bowen; Zhang, Jiawei; Xiao, Shuwen (Frontiers in Energy Research, 2022)
The integrated energy system with electric vehicles can realize multi-energy coordination and complementarity, and effectively promote the realization of low-carbon environmental protection goals. However, the temporary change of vehicle travel plan will have an adverse impact on the system. Therefore, a multi-layer coordinated optimization strategy of electric-thermal-hydrogen integrated energy system including vehicle to grid (V2G) load feedback correction is proposed. The strategy is based on the coordination of three-level optimization. The electric vehicle charging and discharging management layer comprehensively considers the variance of load curve and the dissatisfaction of vehicle owners, and the charging and discharging plan is obtained through multi-objective improved sparrow search algorithm, which is transferred to the model predictive control rolling optimization layer. In the rolling optimization process, according to the actual situation, selectively enter the V2G load feedback correction layer to update V2G load, so as to eliminate the impact of temporary changes in electric vehicle travel plans. Simulation results show that the total operating cost with feedback correction is 4.19% lower than that without feedback correction and tracking situation of tie-line planned value is improved, which verifies the proposed strategy.